Aging and radiation: bad companions. Issue 2 (2nd February 2015) - Hernández, Laia; Terradas, Mariona; Camps, Jordi; Martín, Marta; Tusell, Laura; Genescà, Anna
Summary Aging involves a deterioration of cell functions and changes that may predispose the cell to undergo an oncogenic transformation. The carcinogenic risks following radiation exposure rise with age among adults. Increasing inflammatory response, loss of oxidant/antioxidant equilibrium, ongoing telomere attrition, decline in the DNA damage response efficiency, and deleterious nuclear organization are age‐related cellular changes that trigger a serious threat to genomic integrity. In this review, we discuss the mechanistic interplay between all these factors, providing an integrated view of how they contribute to the observed age‐related increase in radiation sensitivity. As life expectancy increases and so it does the medical intervention, it is important to highlight the benefits of radiation protection in the elderly. Thus, a deep understanding of the mechanistic processes confining the threat of aging‐related radiosensitivity is currently of foremost relevance.